STUDI BAURAN PEMASARAN 4P DALAM KEPUTUSAN PEMBELIAN UNIT LINK PADA PT BHINNEKA LIFE INDONESIA KANTOR CABANG CIKAMPEK, KARAWANG - Dian Ikha Pramayanti (Media Mahardhika, 2019)
Marketing is a business entity activities carried out starting from the process of goods or services to market it to consumers. Marketing has been orienting customer satisfaction. In the marketing process has known the marketing mix, that collection of factors was used enterprises to achieve marketing objectives in the target market. One of the companies appling the marketing mix, is the insurance. In the insurance companies are non-conventional products was known as unit link. That is a product provides the dual purpose of protection (insurance) and investment. The author conducted research at PT Bhinneka Life Indonesia Cikampek Branch Office, with the aim to identify and determine the marketing mix 4P (product, price, process, promotion) that influence purchase decisions products unit link. As well as the most dominant factors selected by respondents. The research method was quantitative the data, obtaining in the form of numbers. The research distributed questionnaires for 45 samples as respondents. The sampling of technique used total sampling technique. In the calculation, the authors used a Likert scale with a score of 1-5 and a scale to determine the category of each factor and statements. Each factor has a three statement. On the of factors product was obtained an average score of 186, factors price was obtained an average score of 177, a factors process was obtained an average score of 179.33, and the factors of promotion was obtained an average score 159.66. All of the factor were in the scale range 153-188, that mean was the category of "agree". This means all of respondents agreed the statements that all the factors influenced purchase decisions unit link at PT Bhinneka Life Indonesia Cikampek Branch Office. While most dominant factors were selected by respondents as factors purchase decision as product earned an average score of 186 in the category of "agree".